Microsurgical versus complex physical decongestive therapy for chronic breast cancer-related lymphoedema - Haas, Yvonne; Williams, Olivia P.; Masia, Jaume; Pons, Gemma; Taylor, Erin M.; Katapodi, Maria C.; Staub, Daniel; Eisenhardt, Steffen U.; Visconti, Giuseppe; Longo, Benedetto; Plock, Jan; Jung, Florian; et al. (Cochrane Database of Systematic Reviews, 2025)
OBJECTIVES: This is a protocol for a Cochrane Review (intervention). The objectives are as follows: To assess the effects of microsurgery versus complex physical decongestive therapy in people with chronic breast cancer-related lymphoedema.
CRIS-Team Scopus Importer:2025-03-14